Interaction Effects and Cognitive Engagements of Collaborative Groups in Online Asynchronous Discussions - Pitagan, Ferdinand B. (Philippine Journal of Education Studies (formerly the Education Quarterly), 2013)
This study analyzes the interaction in collaborative homogeneous and heterogeneous groups in an online asynchronous discussion, examines the level of cognitive engagements in each group and investigates the impact of these groups in interaction effects and cognitive engagements. The research employs the triangulation methodology for the content/transcript analysis and utilizes pre-service teachers as participants. Results show that collaborative homogeneous groups are more conducive for widespread interaction and higher cognitive engagements. An overview of the characteristics and implications of grouping strategies in a computerassisted learning environment is likewise provided.
Keywords: computer-assisted collaborative learning, grouping strategies, interaction effects, cognitive engagements